2021
DOI: 10.1101/2021.03.01.433317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A structural analysis of amyloid polymorphism in disease: clues for selective vulnerability?

Abstract: The increasing amount of amyloid structures offers an opportunity to investigate the general principles determining amyloid stability and polymorphism in disease. We find that amyloid stability is dominated by about 30% of residues localized in few segments interspersed with regions that are often structurally frustrated in the cross-β conformation. These stable segments correspond to known aggregation-nucleating regions and constitute a cross-β structural framework that is shared among polymorphs. Alternative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…This notion comes to add to our recent thermodynamic profiling of the fibril cores of full-length amyloid fibrils, which highlighted that these APR segments provide an extremely conserved framework that commonly stabilises different polymorphs. Furthermore, the same analysis revealed that although additional segments of the polypeptide chain participate in hetero-packing when incorporated in the fibril core, these segments are described by energetically degenerative tertiary packing 40 , thus supporting our findings on the limitations of cross-aggregation interactions within amyloid cores.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This notion comes to add to our recent thermodynamic profiling of the fibril cores of full-length amyloid fibrils, which highlighted that these APR segments provide an extremely conserved framework that commonly stabilises different polymorphs. Furthermore, the same analysis revealed that although additional segments of the polypeptide chain participate in hetero-packing when incorporated in the fibril core, these segments are described by energetically degenerative tertiary packing 40 , thus supporting our findings on the limitations of cross-aggregation interactions within amyloid cores.…”
Section: Discussionsupporting
confidence: 87%
“…1a-1c ). We limited our search to single variants of major APRs as: (i) APRs are the kinetic drivers that promote self-assembly of amyloids 41-44 , (ii) individual amyloid polymorphs share energetic profiles in a sense that they depend on APRs as a common framework of high structural stability to counteract longer regions of structural frustration in their core 40 and (iii) this approach also supports a deeper understanding of potential tendencies, as assignments are performed at a single residue level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although once considered an implausible target for structural biology, recent developments in cryo-electron microscopy (cryoEM) and helical processing have facilitated the structure determination of amyloid fibrils at near atomic resolution 1 . A plethora of experimentally determined structures of both in vitro generated and ex vivo isolated amyloids has revealed a bewildering structural diversity of fiber architectures, including the concept of fiber polymorphs or “strains” of otherwise identical or closely related sequences 25 .…”
Section: Introductionmentioning
confidence: 99%